Manajemen Modal Sosial Lembaga Keuangan Mikro Syariah dalam Mewujudkan Kemaslahatan Umat: Studi Pada Baitul Maal Wat Tamwil di Kudus (Equilibrium: Jurnal Ekonomi Syariah, 2019)
Baitul Maal Wat Tamwil has been growing as the financial institution from grassroot. This study will describe social capital management of Islamic microfinance to realize ummah maslahah. Data was obtained from five Baitul Maal Wat Tamwil in Kudus that are BMT Mitra Muamalat, BMT Harapan Umat, BMT Amanah, BMT Al Amin, and BMT Mahardika. Informants of this research are managers of each BMT. Social capital management is explained based on some aspects contains vision and mission, customer mapping, handling pattern of customer complaints, social activities, human resources training and development model, and education and socialization model. This research approach is qualitative with natural setting to capture essential problems from research object. However, the findings of this research are: (1) formulate vision and mission represent efforts to integrate organizational resources and social values to community welfare; (2) design of training and development programs for employee to increase human resources comprehension in managing products and contracts, and also principles of Islamic finance; (2) educate society to change conventional mindset into Islamic mindset particularly about justice principle and trustworthy; (3) conduct social responsibility through Baitul Maal with donation, scholarship for poor students, home repair, and other assistances; (4) stand with micro-small enterprises, small traders, traditional market traders, farmer, and factory workers; and (5) design risk management through fund reserve system.